PENERAPAN BUDAYA LOKAL TANJAK PADA FASAD BANGUNAN (STUDI KASUS : BANGUNAN INSTANSI PEMERINTAH KOTA PALEMBANG) - Primanisa, Qoyyimah; Rukayah, R Siti (Jurnal Arsitektur ARCADE, 2024)
The application of local cultural elements in architecture is one way to strengthen regional identity and preserve cultural heritage. This research focuses on the use of tanjak, one of the proud symbols of Palembang culture, as the main element in the design of building facades of government agencies in Palembang City. Tanjak, a traditional headdress, was chosen for its strong symbolism in reflecting social status, honor, and local wisdom. This study analyzes how the form and meaning of tanjak are translated into architectural elements on public building facades. The results show that the motifs and forms of tanjak are applied through modern materials such as aluminum and concrete composite panels, with paste and high print techniques resembling reliefs. The application of tanjak not only strengthens the visual character of the building, but also reinforces local cultural identity in harmony with the development of contemporary architecture. The use of this element is expected to be an inspiration in designing public buildings that integrate local cultural symbols more broadly.